Embracing The Vanguard Role: Obstacles Faced by Health Cadres in Fulfilling Societal Responsibilities - Andra Novitasari; Afiana Rohmani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: Health cadres play a crucial role in community development, serving as primary health managers responsible for mobilizing communities and fostering self-help initiatives to improve health outcomes. Despite their significance, challenges such as poor communication leading to missed visits by mothers with toddlers hinder program execution. Understanding and addressing these challenges is essential for establishing a resilient healthcare system that optimizes cadre contributions.Method: A qualitative, phenomenological approach was employed in this study. In-depth interviews were conducted with 11 diverse participants, including the Head of the Public Health Center, the Coordinator of Health Cadres, Health Cadres, and Community Members. Informant selection utilized purposive techniques and snowball sampling, with an interview guide containing open-ended questions as the research instrument. The data analysis followed a descriptive approach based on the Miles and Huberman model.Results: Challenges faced by health cadres varied across regions, encompassing factors such as differing community participation levels, heavy administrative tasks, and conflicts among cadres. Despite these challenges, most cadres exhibited high commitment, motivation, and familial support, mitigating potential issues. Each cadre adopted a unique approach to anticipate and address challenges associated with their roles. Regular coaching from Public Health Centers and implementing simplified administrative systems were identified as potential strategies to enhance cadre performance.